Khawarij and the Sunnah of the Prophet: Genealogy of Inkar al-Sunnah in the Early History of Islam - Taufik, Wildan; Wendry, Novizal; Majid, Abdul; Isnaeni, Ahmad (Journal of Hadith Studies, 2018)
This article discusses the Khawarij sect and the Sunnah of the Prophet. The discussion focuses on the genealogy of the Ink?r al-Sunnah movement during the early period of Islamic history. Using a literature review method, this article finds that, as an early Islamic sect, the Khawarij were not only a physical rebellion movement but also transformed into an intellectual movement. This article concludes that one of the intellectual products of the Khawarij sect is the dictum "la hukma illa li al-Lah" ("There is no judgment except for Allah"). Implicit in this phrase is their emphasis on the Qur'an as the primary religious perspective, while having a minor view towards the Sunnah of the Prophet. Therefore, some scholars have referred to the Khawarij as holding an Inkar al-Sunnah perspective. They were labeled Qur’aniyyun because they viewed religious discourse in a black-and-white manner. The following discussion provides a historical-analytical exploration of the genealogy of the Khawarij sect and their religious views.